An Architecture for M2M Communications over Cellular Networks Using Clustering and Hybrid TDMA-NOMA - Rozario, Anthonya Barsha (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2019.